AN ANALYSIS OF PRESUPPOSITION IN “OUIJA : ORIGIN OF EVIL MOVIE” : PRAGMATICS APPROACH - nur a'la, sillatul dwi; Zakrimal, Zakrimal (SCIENTIA JOURNAL, 2020)
This research is a case study which will discuss about presupposition in the film "Ouija: Origin of Evil". It helps to know the types of presuppositions and dominant types of presuppositions in the Ouija movie. Then the data is analyzed using pragmatic qualitative methods. And the researchers used Yule (1996) Theory to analyze the presuppositions in the Ouija movie. The results of the analysis are presented descriptively with context so that the meaning of pragmatic presuppositions can be released. From the results of the analysis, researchers will find there are 6 types of presuppositions by Yule (1996), namely Existential Presuppsition, Structural Presuppositions, Factive Presuppositions, Non-Factive Presuppositions, Lexical Presuppositions, and Counter-Factual Presuppositions. Structural type of presuppositions appear most often, 5 times. Structural presupposition is a type that is often used in Ouija's story of one of the main characters in the Oujia movie, often using sentences related to questions in conversations with others. Related to the conversation can be assumed as an answer or information the existence of a truth that occurs by the speaker. Keywords: presupposition, types presupposition, movie